Probiotics Alter the Microbial and Behavioral Consequences of Methamphetamine Exposure in a Sex-Selective Manner - Shadab Forouzan; Kristi L. Hoffman; Therese A. Kosten (MDPI AG, 2024)
Methamphetamine use disorder (MuD) is a global health problem, with no FDA-approved medications. Our prior work demonstrated that repeated methamphetamine exposure alters the gut microbiota in male rats and results in depressive-like behaviors. In this study, we extend our findings to females and determine whether probiotics block these effects. Male and female rats were administered methamphetamine (2 mg/kg; SC) or saline twice daily with either a combination of two probiotics (Lactobacillus helveticus R0052 and Bifidobacterium longum R0175) or placebo solution for 14 days. Fecal samples were collected at baseline and other days after treatment cessation. Tests of anxiety- and depressive-like behaviors were conducted using open-field and forced-swim assays. Methamphetamine induced anxiety-like behavior in females and anxiety-like and depressive-like behaviors in males. Probiotics blocked the depressive-like effect in males but did not alter anxiety-like effects in either sex. Methamphetamine exposure decreased levels of alpha diversity in both sexes, but sex differences were seen in the ability of probiotics or methamphetamine to alter levels of various bacteria. These findings support the role of the gut-brain microbiome in the depressive effects of repeated methamphetamine exposure in males, suggesting that probiotics may be a viable treatment option for MuD.